PENGARUH PEMBERIAN KONSELING DENGAN MEDIA VIDEO DAN BOOKLET TERHADAP PENINGKATAN PENGETAHUAN KONSUMSI TABLET FE PADA IBU HAMIL ANEMIA - Rohani; Rena Astuti; Veradilla (Jurnal Kesehatan dan Pembangunan, 2023)
Anemia can occur due to a lack of iron or Fe, a lack of Fe can cause a lack of Hemoglobin (HB). The dominant factor affecting the lack of hemoglobin is the knowledge factor. With counseling about anemia during pregnancy, it is hoped that pregnant women will pay attention to how important the health of pregnant women themselves and their fetuses is. Media that can be used in health education are video media and booklets. The research objective was to determine the effect of providing counseling using video media & booklets on increasing knowledge of Fe tablet consumption in anemic pregnant women at the Soraya Clinic Palembang in 2022. This type of research is a quantitative study using a quasi-experimental research design and with a pretest-posttest with control design. group design with a sample of 30 people. The results obtained by the paired test statistical test obtained a p value = 0.000 <0.05 meaning that there was an effect of providing counseling with video media and booklets on knowledge of consuming Fe tablets in anemic pregnant women at PMB Soraya 2022 Palembang. Suggestions for health workers, especially midwives, can use video media and booklets in providing counseling to pregnant women, especially to increase knowledge of Fe tablet consumption in anemic pregnant women, so that pregnant women know the importance of consuming Fe tablets regularly and avoid anemia.stage can apply a massage counter pressure as a method of reducing labor pain in the first stage of labour.